Probabilistic Assessment of Available Transfer Capability Incorporating Load and Wind Power Uncertainties - Hala W. Reyad; Medhat Elfar; E. E. El-Araby (IEEE Access, 2023)
This study proposes an available transfer capability (ATC) assessment approach in an intraday market that would enable wind energy participants to raise their level of integration without exposing them to high risk. The presented methodology allows the transmission system operator (TSO) to assess ATC near to the real state while considering voltage stability concerns as well as the uncertainties of the forecasted load and wind power. The proposed formulation is designed so that the existing VAR sources are appropriately exploited during the ATC assessment to maximize its anticipated value and boost the transaction between various zones. To alleviate the complexity of analyzing N-1 contingencies in the ATC estimation, a linear sensitivity technique is applied for ranking the most severe contingencies to be examined carefully. A two-level hybrid algorithm using the primal-dual interior point method (PDIPM) and an improved grey wolf optimizer (IGWO) is suggested for solving the problem. The performance of the proposed approach has been evaluated by its application on IEEE 30- reliability test system (RTS). The outcomes confirm the viability of the proposed approach for optimizing ATC value for various transactions through the best use of installed VAR devices, considering different locations of wind farms. The obtained findings also demonstrate the effectiveness of the suggested method for determining the most severe contingency associated with each scenario under consideration.